Bartonella henselae Infective Pulmonic Valve Endocarditis Triggering ANCA-Associated Crescentic Necrotizing Glomerulonephritis - Natalia Nombera-Aznaran; Christopher Blais; J. Martin Rodriguez; Yihan Wang; Juan Carlos Q. Velez (Annals of Internal Medicine: Clinical Cases)
Bartonella species is the third leading cause of infective endocarditis–associated glomerulonephritis and the most common cause among culture-negative cases. Most cases involve tricuspid, aortic and mitral valves. We report an unusual case of pulmonic valve infective endocarditis causing acute kidney injury due to antineutrophil cytoplasmic antibody–associated pauci-immune glomerulonephritis. Urinary sediment microscopy findings raised clinical suspicion before fever or other signs of infection appeared. The case also highlights the importance of recognition of histopathologic patterns of injury in infective endocarditis–associated glomerulonephritis, the caveats about testing for Bartonella species infections, and the diagnostic value of nuclear medicine in this setting.